Monitoring mammals in airfield environments; a case study of the Irish hare at Dublin Airport - Ball, Samantha (University College Cork, 2022)
The number of reported wildlife-aircraft collisions (i.e., strikes) with mammal species is increasing globally with severe consequences for passenger safety, industry economics and wildlife populations. Despite this, little research has been conducted on the class Mammalia in airfield environments, with strike mitigation research efforts predominantly focused on avian species. This thesis addresses some of the wildlife hazard issues faced by the aviation industry, specifically looking to mammal species. The thesis focuses on developing ecological survey methods for mammals in airfields and exploring the role of ecological data in informing strike risk. The Irish hare (Lepus timidus hibernicus) population at Dublin airport is used as a population case study to assess survey methods in an airport environment, throughout. As little is known about mammal strikes on a global scale, strike records with mammals from available literature and national aviation authorities are collated in chapter 1. These data highlighted that mammal strikes are widespread and identify 42 mammal families involved in strike events in 47 countries and demonstrate that reported mammal strike events have been increasing by up to 68% annually. Looking to mammal management measures on a European scale for chapter 2, the most successful mammal mitigation measures were identified as: (i) the management of watercourses within the airfield; (ii) the implementation of specific grass cutting regimes (94.4%) and (iii) the management of waste products at the airfield so as not to attract or sustain wildlife (93.8%). Utilising historical strike data in chapter 3, it was demonstrated that hare strikes have been increasing by an average of 14% annually at Dublin Airport with over 340 recorded wildlife strikes since 1997. The kinetic energy of such an event (10,576 J) is substantial enough to inflict damage to the landing gear of an aircraft, although this has never been reported to have occurred. As the basis of effective wildlife management practices ...